Point-of-Care Testing for Pharyngitis in the Pharmacy - Sabiha Essack; John Bell; Douglas Burgoyne; Wirat Tongrod; Martin Duerden; Aurelio Sessa; Attila Altiner; Adrian Shephard (MDPI AG, 2020)
Pharyngitis (also known as sore throat) is a common, predominately viral, self-limiting condition which can be symptomatically managed without antibiotic treatment. Inappropriate antibiotic use for pharyngitis contributes to the development and spread of antibiotic resistance. However, a small proportion of sore throats caused by group A streptococcal (GAS) infection may benefit from the provision of antibiotics. Establishing the cause of infection is therefore an important step in effective antibiotic stewardship. Point-of-care (POC) tests, where results are available within minutes, can distinguish between viral and GAS pharyngitis and can therefore guide treatment in primary healthcare settings such as community pharmacies, which are often the first point of contact with the healthcare system. In this opinion article, the evidence for the use of POC testing in the community pharmacy has been discussed. Evidence suggests that pharmacy POC testing can promote appropriate antibiotic use and reduce the need for general practitioner consultations. Challenges to implementation include cost, training and 'who prescribes', with country and regional differences presenting a particular issue. Despite these challenges, POC testing for pharyngitis has become widely available in pharmacies in some countries and may represent a strategy to contain antibiotic resistance and contribute to antimicrobial stewardship.